Positioning Human Microbiome DTC Tests On the Search for Health, Data and Alternatives Amid the Financialisation of Life (Medicine Anthropology Theory, 2021)
Early during my fieldwork on the social life of the microbiome in Toronto, I was asked ‘Do you believe in microbiome testing?’ This question invited me to evaluate the science of the direct-to-consumer (DTC) test. In this Position Piece, I consider this question in a more expansive manner so as to position the test in its social and economic context. The distribution and public uptake of such a DTC test require scientific expertise but also marketing, capital investments, and clinical labour. This test requires consumers to do the work of stool collection and the reproductive labour of diet changes in their domestic spaces. I have learned that the microbiome is part of the quest for alternative ways of living and being healthy. Broadening the question to consider more than just the science expands the frame from one of scientific efficacy and individual consumption to one that considers the financialisation of health and the politics and environments of post-Pasteurian and post-industrial contexts.